Pengaruh Financial Distress dan Leverage Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Arum, Sekar Tiyas; Hakim, Heikal Muhammad Zakaria (Peneliti.net, 2023)
This study aims to determine the effect of financial distress and leverage on company value in banking subsector companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study was 20 banking subject companies listed on the Indonesia Stock Exchange by sampling using purposive sampling. The research variable consists of company value as a dependent variable which is proxied with Price to Book Value (PBV). The independent variables consist of financial distress and leverage proxied with Z